2007
DOI: 10.1038/modpathol.3800717
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles associated with aggressive behavior in Merkel cell carcinoma

Abstract: Primary neuroendocrine carcinoma of the skin, or Merkel cell carcinoma, is the most aggressive cutaneous neoplasm. In spite of its similarities to small cell carcinomas from other locations, Merkel cell carcinoma shows many peculiarities probably related to its epidermal origin and the etiologic role of UV radiation. We have immunohistochemically investigated 43 markers on a tissue microarray in which 31 surgically resected Merkel cell carcinomas were represented. Of these, 15 patients remained free of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 55 publications
6
59
0
2
Order By: Relevance
“…In our study of Merkel cell carcinoma, we observed diffuse and weak expression of VEGF in 480% of cases (unpublished data), which is similar to data recently published examining 43 markers on 31 cases of Merkel cell carcinoma via tissue microarray analysis. 49 However, the staining we observed for VEGF was independent of KIT expression levels, suggesting that multiple pathways may exist which activate VEGF expression. The data of Fernandez-Figueras et al 49 also suggests a likely role for VEGF in tumor progression and the potential benefit of using anticancer treatments targeted against VEGF and other members of its signaling pathway.…”
Section: Discussionmentioning
confidence: 69%
“…In our study of Merkel cell carcinoma, we observed diffuse and weak expression of VEGF in 480% of cases (unpublished data), which is similar to data recently published examining 43 markers on 31 cases of Merkel cell carcinoma via tissue microarray analysis. 49 However, the staining we observed for VEGF was independent of KIT expression levels, suggesting that multiple pathways may exist which activate VEGF expression. The data of Fernandez-Figueras et al 49 also suggests a likely role for VEGF in tumor progression and the potential benefit of using anticancer treatments targeted against VEGF and other members of its signaling pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Our results conWrm data presented by Garcia-Caballero and colleagues (1989) who described the presence of synaptophysin in MCs of the pig snout. Interestingly, synaptophysin was also detected in a large proportion of MCC (Acebo et al 2005;Fernandez-Figueras et al 2007;Llombart et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The frequent heterozygous loss of chromosome 10 or the long arm of chromosome 10 in MCC suggests that the tumor suppressor PTEN encoded there plays a relevant role [37]. A recent study using MCC tissue arrays to measure the expression of various proteins (especially matrix metalloproteinases) revealed that PTEN could hardly be identified in the samples examined, which could indicate inactivation of the second allele, e.g., by epigenetic mechanisms [38]. The epigenetic silencing of another tumor suppressor gene in MCC had been recently reported [39].…”
Section: Pathogenesismentioning
confidence: 99%